Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Inkuiri Terbimbing pada Materi Sistem Pertahanan Tubuh Siswa Kelas XI SMA/MA - Harahap, Yulia Fatma; Khairuna, Khairuna; Rohani, Rohani (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
The purpose of this study was to develop guided inquiry-based worksheets on the material of the body’s defense system by testing the validity, practicialy, and effectiveness of the worksheets. The research was conducted at the MAN 2 LABURA school. The research method used is Research and Development (R&D) research with a 4D model (define, design, develop, disseminate). The results of this study indicate that the guided inquiry-based LKPD develop obtains very practical criteria with a percentage of 79% (media expert), 75% (material expert), and 100% (biology teacher response), and 91% (student response). LKPD is said to be effective based on the n-gain value with a score of 0,81 in the high category. Based on explanation above, the guided inquiry-based LKPD developed is feasible, practical, and effective for use in the learning process in the classrom on biology learning material for the body’s defense system. Keyword: Guided Inquiry, LKPD, Body’s Defense System